Biomimetic Synthesis of Equisetin and (+)‐Fusarisetin A. Issue 39 (12th August 2013) - Yin, Jun; Kong, Lili; Wang, Cheng; Shi, Yingbo; Cai, Shujun; Gao, Shuanhu
Abstract (+)‐Fusarisetin A belongs to a group of acyl tetramic acid natural products that show potential anticancer activity. Equisetin, a biogenetically related acyl tetramic acid, contains the basic skeleton of (+)‐fusarisetin A. We proposed that equisetin and (+)‐fusarisetin A share a biosynthetic pathway that starts with naturally occurring (S)‐serine and an unsaturated fatty acid. In support of this hypothesis, we have demonstrated that a cyclization sequence involving an intramolecular Diels–Alder reaction followed by a Dieckmann cyclization of polyenoylamino acid yielded equisetin. The aerobic oxidation of equisetin, promoted by either MnIII/O2 or a reactive oxygen species (ROS) produced by visible‐light chemistry, gave peroxyfusarisetin, which could be easily reduced to (+)‐fusarisetin A. We report herein detailed information on the biogenetic synthesis of equisetin and (+)‐fusarisetin A.